The seaplane on final approach : a novel - Rukeyser, Rebecca, 1985- (Doubleday, 2022)
"A 'lusty, funny, heart-breaking' (Carmen Maria Machado) debut about a sex-obsessed young woman seeking out experience on a remote Alaskan homestead. Tourists arrive all summer, by boat or seaplane, at Lew and Maureen Jenkins's Lavender Island Wilderness Lodge in the Kodiak Archipelago, expecting adventure. But the spontaneity of their authentic 'Alaskan wilderness' experience is meticulously scripted, except when real danger rears its head. Lew and Maureen's lodge is failing, as is their marriage. Eighteen-year-old Mira has been hired for the season as the lodge's baker and housekeeper. But she's also busy gleefully nursing twin obsessions: building a working theory of American sleaze and pursuing a young fisherman she's determined is the embodiment of all things deliciously sleazy. Her plans become more perverse and elaborate, even as life on Lavender Island starts to unravel. By midseason, it becomes clear that Lew, the jovial, predatory patriarch of the lodge, has turned his sexual attentions to another young employee. As the mood of the lodge spirals into chaos, the inhabitants of the lodge realize just how isolated Lavender Island really is. Hilarious, sensual, and charged with menace, The Seaplane on Final Approach brilliantly illuminates the mirage-thin line between the artificial and the feral, and between a young woman's potential and her actual becoming. In this daring and psychologically razor-sharp debut, Rukeyser's characters tear aside the façade of good manners to reveal all of our deepest needs and naked desires"--